2015
DOI: 10.1017/s1368980015000257
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast skipping and the risk of type 2 diabetes: a meta-analysis of observational studies

Abstract: Objective: Breakfast skipping has been reported to be associated with type 2 diabetes (T2D), but the results are inconsistent. No meta-analyses have applied quantitative techniques to compute summary risk estimates. The present study aimed to conduct a meta-analysis of observational studies summarizing the evidence on the association between breakfast skipping and the risk of T2D. Design: Systematic review and meta-analysis. Setting: Relevant studies were identified by a search of PubMed, Embase, Web of Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
112
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 35 publications
2
112
0
11
Order By: Relevance
“…Skipping breakfast has been associated with markers of impaired glucose metabolism, including elevated hemoglobin A 1c , 44 higher fasting plasma glucose 58 and all-day postprandial hyperglycemia, 59,60 and a higher rate of impaired fasting glucose. 28 In contrast, HOMA-IR did not differ statistically between breakfast skippers and eaters.…”
Section: Breakfast Skipping and Other Cvd Risk Factorsmentioning
confidence: 99%
“…Skipping breakfast has been associated with markers of impaired glucose metabolism, including elevated hemoglobin A 1c , 44 higher fasting plasma glucose 58 and all-day postprandial hyperglycemia, 59,60 and a higher rate of impaired fasting glucose. 28 In contrast, HOMA-IR did not differ statistically between breakfast skippers and eaters.…”
Section: Breakfast Skipping and Other Cvd Risk Factorsmentioning
confidence: 99%
“…Studies of adolescent children in the both US and Australia have shown that breakfast consumption is associated with lower body mass index (BMI) [5,6], and in Canada it has been estimated that not eating breakfast every day nearly doubled the odds of being overweight at 4.5 years of age [6,7]. A recent meta-analysis found that breakfast skipping is associated with an increased risk of developing type 2 diabetes [8]. In Australia, childhood breakfast skipping was associated with both higher waist circumference and negative effects on cardio-metabolic health markers in adulthood [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adolescents who consume breakfast have been shown to have better overall quality of life, school attendance and academic achievement [3,4,5,6]. Concomitantly, studies have linked skipping breakfast to adverse health outcomes of overweight and obesity, type 2 diabetes mellitus, and metabolic syndrome [7,8,9,10]. Despite the importance of breakfast consumption, a high prevalence of skipping breakfast among children and adolescents is widely reported in many countries across the world [11,12].…”
Section: Introductionmentioning
confidence: 99%